Management practices to offset the declining trend of alfalfa hay production - Michael Baidoo; Chandan Shilpakar (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Agriculture in the United States (US) is a major industry, which is the net exporter of food. The livestock sector is a centerpiece of the industry, and the base for this sector is forage resources. A forage-livestock production system is the largest economic agricultural sector in the US, and it feeds millions of people each day. More than half of the US land area has been devoted to cultivating forage crops mainly for livestock feed. In spite of the several options of forage crops available to growers to choose for production, the suitable choice often relies on the quality and quantity of hay that can be produced by the crop to meet production objectives. Alfalfa (Medicago sativa L.), the world's premier forage crop, remains to be the number one choice for livestock feed due to its ability to produce high yields of sustained nutritive value. However, recent data shows that on the national average, alfalfa hay yields are decreasing with a direct and indirect consequent effect on the nation's economy. Implementing efficient agronomic management practices in the alfalfa production system is a step in the direction of successful production. Along with the initial soil fertility status, integrating production factors including phosphorus and potassium fertilization, cultivar, and harvest management can be advantageous to ensure an improved physiology of alfalfa for greater hay production in the long term. Core ideas • Alfalfa hay production in the US has been decreasing over the past 3 decades. • Reduced hay yields of alfalfa pose significant challenges to the forage-livestock production system. • There is a critical need to continually improve the productivity of alfalfa. • Appropriate agronomic amendments present opportunities to enhance alfalfa production. • Annual application of phosphorus and potassium to high-yielding alfalfa cultivar based on the initial soil fertility status, and harvest time have a great potential for higher hay yields.